The church is an active participant in the establishment of civil society (Maidan 2013-2014). - Gorkusha, Oksana (Ukrai͏̈ns'ke relihijeznavstvo, 2016)
The direct immersion in the fateful event of the Maidan for Ukraine made it possible to keep a conscious mind on the pulse of its course while at the same time contributing to a critical understanding of its information display. In the title of our book, "Maidan and the Church: Chronicle of Events and Expert Evaluation" (K, 2014), there was fixed a problem core, on which we were trampled by all illustrative documents and expert assessments: the ownership of the Maidan (and it is an effective model of civil society that emerged in in response to modern Ukraine and in opposition to the rude attempts by the authorities to stop the historical and spiritual progress of the people, encapsulating Ukraine in the previous forms of life and consciousness) and the Church - a religious community formed in accordance with spiritual needs and requests from civil society and becomes an inalienable, equal subject.